We think of you as an angel : Shaul Weingort and the rescue of Jews during the Holocaust - Kadosh, Sara (Yad va-shem, International Institute for Holocaust Research, 2019)
[This book] sheds light on the previously unknown story of Shaul Weingort's efforts to create an aid network that would deliver food, provide South American passports, and give hope to his family and hundreds of other Polish Jews in an attempt to save their lives [during World War II]. (back cover)